2020
DOI: 10.1111/1744-7917.12867
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification and characterization of long non‐coding RNAs in Tribolium castaneum

Abstract: Long non-coding RNAs (lncRNAs) are poorly understood in insects. In this study, we performed genome-wide analysis of lncRNAs in Tribolium castaneum by RNAseq. In total, 4516 lncRNA transcripts corresponding to 3917 genes were identified from late embryos, early larvae, late larvae, early pupae, late pupae and early adults of T. castaneum, including 3152 novel lncRNAs and 1364 known lncRNAs. These lncRNAs have few exons and transcripts, and are short in length. During development, they exhibited nine different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 84 publications
2
17
0
Order By: Relevance
“…For example, lncRNAs were identified in different developmental stages of T. castaneum. These results suggested that lncRNAs could act on the metabolic enzymes related to development [9].…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…For example, lncRNAs were identified in different developmental stages of T. castaneum. These results suggested that lncRNAs could act on the metabolic enzymes related to development [9].…”
Section: Introductionmentioning
confidence: 84%
“…Molting is an important event in the development process of arthropods, which undergoes a series of physiological changes such as the forming and degradation of the cuticle, internal tissue apoptosis and remodeling, and other physiological processes [35]. lncRNA expression in the biological processes of development have been examined in insects [7,9]. In the mites, lncRNA has been identified in many physiological processes of mites such as V. destructor [33], T. cinnabarinus [34], and Dermatophagoides farina [36].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even though lncRNAs have been discovered from many insect species, most of our knowledge about the functional aspect of insect lncRNAs comes from studies in Drosophila melanogaster . Besides Drosophila , lncRNAs have also been reported in Anopheles gambiae [ 19 ], Apis mellifera [ 20 ], Bombyx mori [ 21 ], and Tribolium castaneum [ 22 , 23 ]. With the advent of next-generation sequencing (NGS) technologies, large numbers of lncRNAs have been identified, but most of them remain functionallyunvalidated [ 24 ].…”
Section: Long Non-coding Rnas (Lncrnas)mentioning
confidence: 99%